2017
DOI: 10.1080/14786419.2017.1360881
|View full text |Cite
|
Sign up to set email alerts
|

Anxiolytic potency of iridoid fraction extracted from Valeriana jatamansi Jones and its mechanism: a preliminary study

Abstract: Valeriana jatamansi Jones (V. jatamansi) has been widely used for treating anxiety and its mechanism involves many aspects including GABA level. This study aimed to evaluate the anxiolytic potency of an iridoid fraction extracted from the radix and rhizomes of V. jatamansi. The iridoid fraction was extracted by using D101 resin; its major components were analysed preliminarily by thin layer chromatography, ultraviolet spectrophotometry and high-performance liquid chromatography; and its anxiolytic effects at 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…V. jatamansi is a famous TCM herb that has been wildly used in Asia and Europe for thousands of years. A previous study from our laboratory reported that IRFV possesses various effects, such as neuroprotective effects, antifree radicals, anti-inflammatory, and even antianxiety (Yan et al, 2010) (Zhang et al, 2018). It may also have antidepressant effects.…”
Section: Discussionmentioning
confidence: 93%
“…V. jatamansi is a famous TCM herb that has been wildly used in Asia and Europe for thousands of years. A previous study from our laboratory reported that IRFV possesses various effects, such as neuroprotective effects, antifree radicals, anti-inflammatory, and even antianxiety (Yan et al, 2010) (Zhang et al, 2018). It may also have antidepressant effects.…”
Section: Discussionmentioning
confidence: 93%
“…Traditional Chinese medicine studied in different phases of clinical trials for their potential in the treatment of fear-, anxiety-, and trauma-related disorders is adopted. Furthermore, several experimental studies suggest that ZZX ( Jugran et al, 2019 ) and its active ingredient valtrate ( Zhang et al, 2018 ) play a role in several forms of nervous system diseases, including negative emotions related to anxiety and depression. Clinic-based studies suggest that patients with depression benefit from 70% ethanol extract of ZZX ( Bhattacharyya et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with flumazenil significantly reduces anxiolytic-like effects, but treatment with V. jatamansi did not affect the spontaneous activity in mice. The study concludes that the compound V. jatamansi can be a better choice for anxiolytic action than producing sedation [26,27].…”
Section: Anxiolytic Activitymentioning
confidence: 93%